Sistem Pendukung Pengambilan Keputusan Penerimaan Dosen Dengan Metode AHP - Nur Hidayati; Tri Waluyo; E.I.H. Ujianto (Bianglala Informatika, 2019)
One of the problems that occurred at the University of Technology Yogyakarta was that the selection process of prospective lecturers was less effective. The problem is due to the development of institutions that increase the number of study programs so that the number of students is increasing. For this reason, from the side of the teaching staff (lecturers), it is also necessary to increase the ratio of lecturers and students according to the applicable rules. In the lecturer selection process there are several requirements that must be met, namely the level of education, work experience, achievements. With some of the assessment criteria the selection committee will have difficulty making decisions and tend to rely on subjectivity. In this study the author uses the AHP method, which is one of the ranking methods to help determine the right lecturer.